Inclusive Fitness Affects Both Prosocial and Antisocial Behavior: Target Gender and Insult Domain Moderate the Link between Genetic Relatedness and Aggression - Amanda N. Gesselman; Gregory D. Webster (Evolutionary Psychology, 2012)
Although prior research has examined the relationship between genetic relatedness and helping behavior (Burnstein, Crandall, and Kitayama, 1994), less is known about its role in aggressive responses to insults ( Fitzgerald and Ketterer, 2011 ). Drawing on inclusive fitness theory ( Hamilton, 1964 ) and the Kinship, Acceptance, and Rejection Model of Altruism and Aggression (KARMAA; Webster, 2008 ; Webster et al., 2012 ), we designed a 2 (participant gender) × 2 (target gender) × 2 (insult: status vs. reproductive) × 3 (relatedness: stranger vs. cousin vs. sibling) between-person experiment in which 489 participants (a) read vignettes in which a stranger, cousin, or sibling was insulted and (b) reported their emotional reaction and retaliation likelihood (six-item α= .91) in response to the insult. Consistent with theory and prior research, men were significantly more aggressive than women, and people were significantly more aggressive responding to insults against kin than non-kin. These findings support theoretically-derived, dynamic, and domain-specific links among insults, gender, relatedness, and aggression.